Perancangan Alat Press Ubi Parut Tipe Tabung Dengan Sistem Hidrolik - Saputra, Zemi Jaka; Balaka, Ridway; Rinova, Raden (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2020)
Cassava as a food ingredient has various processing methods, one of which is grated and then squeezed. In the process of squeezing grated potatoes, it is still mostly done manually. This method, besides being cost-effective, does not require certain skills, but it takes quite a long time to get the desired results. So, there is a need for innovation to facilitate the process of squeezing grated potatoes. Therefore, a research was conducted on the design of a tube type grated sweet potato press with a hydraulic system. The purpose of this study was to simplify and speed up the process of squeezing grated potatoes. This research was conducted by designing using an inventor application by considering the use of materials as a press machine construction. The area of the tool frame steel profile is 30 mm x 30 mm x 4 mm, A = 2.27 cm2. The force acting on the tube when pressing the sweet potato F = 1,236,3 kgf. Tensile force on steel support Fp = 309.075 kgf. Tensile stress that occurs t = 1361.56 N/cm2. Weld area A = 180 mm2. Welded joints in the tool receive a load of P = 3090.7 N (309.07 kg.f) and the welded joint receives a shear load of = 8585 N/mm2 (or 858.5 N/cm2).Keywords: Design, press tools, hydraulics